EVALUASI IMPLEMENTASI KARTU OBSERVASI BAHAYA - Suryatno S (Jurnal Kesehatan Masyarakat Indonesia, 2015)
Hazard Observation Cardis tool to assist of inspection process of potensial hazard to employee. Causes of accidents are 88% due to unsafe behavior, 10% due to unsafe condition and 2% unknown cause. Implementation hazard observation card program is behavior shape of safety culture to effort prevention and controlling accident risk.Porpose :to evaluate implementation quality of hazard observation cardat MontDOr Oil Tungkal Ltd. Method :this quantitative of research is apply with survey method and cross-sectional design. Independent variable are education, work period and position. The dependent variable is implementation quality of hazard observation card. Sample research are staff and non-staff employees of MontD'Or Oil Tungkal Ltd with 67 respondents. Analysis data using Kruskal-Wallis and Mann whiteney test.Result : The most study of respondents are Senior High School (52.2%), the most work period of respondents are ? 5 years (64,2%), the most position of respondents are non staff (70.1%). Relationship test between education and implementation quality of hazard observation card obtained p-value 0.008, relationship testbetween work period and implementation quality of hazard observation card p-value0.507 and relationship test between position and implementation quality of hazard observation card p-value 0,001. Conclusion : implementation quality of hazard observation cardrelated with study and position.